The effect of microfinance factors, social capital and vulnerability on women-empowerment in Southern Punjab, Pakistan - Hameed, Waseem Ul (2019)
Women-empowerment is one of the crucial issues worldwide. In Pakistan, women are bound to customs, norms, beliefs which are unique. These issues are found to promote social problems and hinder the economic contribution by Pakistani women. Due to these cultural issues, women are not allowed to take part in income generating activities like micro-enterprises and because of these issues, gender discrimination is increasing which increases the poverty level among women and decreases the women-empowerment. Consequently, the employment-to-population ratio of women is only 22.1% in Pakistan which is quite low. To address these issues, the current study highlighted microfinance as an effective medium with the support of three forms of capital (financial capital, human capital, social capital). These capitals are the key to the success of Pakistani women. The current study also examined the moderating role of vulnerabilities (social, economic, environmental, political) between microfinance factors and women-empowerment. Data was collected from female clients of microfinance institutes. By using area cluster sampling technique, Southern Punjab was divided into five various clusters and respondents were selected through random sampling technique. A survey was carried out, and 500 questionnaires were distributed in selected clusters. Partial Least Square (PLS)-Structural Equation Modeling (SEM) was used to analyze the data. The results of PLS analysis shows that microfinance factors namely micro-credit, micro-saving, microinsurance and micro-training/skill development have significant positive contribution to women-empowerment. Moreover, it is found that social capital is also important to enhance women-empowerment. Vulnerabilities aspects such as social vulnerability, economic vulnerability, environmental vulnerability and political vulnerability have adverse effects on women-empowerment. Finally, this study could be beneficial for microfinance institutes, state bank of Pakistan and government in making the strategies to enhance women-empowerment by mitigating vulnerability issues.